Determination of genotoxic effects of organochlorine pesticides in wheat (triticum aestivum l.) by comet assay - AYDİN, YILDIZ (Nova, 2019)
DETERMINATION of GENOTOXIC EFFECTS of ORGANOCHLORINE PESTICIDES in WHEAT (Triticum aestivum L.) by COMET ASSAYMelek Adiloğlu Öztürk1,Yıldız Aydın1* 1Department of Biology, Faculty of Science and Letters, Marmara University, Istanbul, TurkeyAbstractDue to the detection of pesticides in underground and surface waters in many agricultural regions of the world, the environmental dimension of pesticide use is an important issue discussed today. Continuous use of pesticides in agriculture causes genetic resistance to pests. Pesticides threaten the ecosystem by altering the structure and species distribution of the ecosystem and disrupting the normal balance between food chains and therefore need to be monitored under strict supervision. In this study, our aim was to determine the genotoxic effects of endosulfan (ES) pesticide at different time and concentrations in wheat (Triticum aestivum L.). Leaf samples were taken from two-week old wheat seedlings of the negative control (Hoagland solution), positive control (Hoagland solution containing 0.1% H2O2) and different concentrations (1 g/L, 2 g/L and 4 g/ L) of ES in treated groups at 6h, 12h and 18h and were examined by comet technique (single cell gel electrophoresis).DNA damage levels were found that increase significantly after the ES application to wheat seedling at all the time and the concentrations that evaluated by comet analysis. In wheat seedlings, the highest DNA damage (% Tail DNA:50, Olive tail moment: 0.34) were determined at 12h of 2 g/L ES concentration (p<0.001). While a non-linear decrease with time in the level of DNA damage were detected in all groups at the end of the 6h, 12h, and 18h of ES treatment by comparing with comet data, the DNA damage was increased in 2 g/L ES at 12h (% Tail DNA:50, Olive tail moment: 0.34) comparing with 6h.The obtained results of this study demonstrated that the ES is a genotoxic agent causing DNA breaks in wheat. Also, the results related with decrease in the level of DNA damage obtained from this study will contribute to the determination of the spraying and harvesting time as well as the determination of the appropriate concentrations in the countries using this pesticide. This work was supported by the Research Foundation of Marmara University (BAPKO no. FEN-C-031210-0285). * Corresponding Author Email: ayildiz@marmara.edu.tr.
Keywords: Yaşam Bilimleri; Biyoteknoloji; Bitki Biyoteknolojisi; Temel Bilimler; Life Sciences; Biotechnology; Plant Biotechnology; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Mikrobiyoloji; ÇOK DİSİPLİNLİ BİLİMLER; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; MICROBIOLOGY; MULTIDISCIPLINARY SCIENCES; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Multidisciplinary; Applied Microbiology and Biotechnology; Molecular Medicine